Kepemimpinan Perempuan dalam Masyarakat Patriarkal: Dinamika Sosio-Kultural Pemimpin Perempuan di Aceh Besar - Rakhmawati (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to analyze the factors that contribute to the emergence of female leaders in Aceh Besar, a region known for its strong adherence to patriarchal values. Despite the socio-cultural constraints, five women have attained strategic and sacred leadership positions, challenging traditional gender norms. Employing a qualitative approach, this research utilizes a phenomenological method to explore the lived experiences of these female leaders within the socio-cultural dynamics of Aceh Besar. Data were collected through in-depth interviews and observations, allowing for a comprehensive understanding of the underlying factors that support their leadership roles. The findings reveal that the rise of female leaders in Aceh Besar is driven by a combination of intellectual capacity, social capital, and active participation in public affairs. Their leadership roles signify a shift in societal perceptions, demonstrating that women are increasingly recognized as capable and influential figures in various sectors. Furthermore, their success highlights the evolving nature of gender roles in Aceh Besar, where women are gradually gaining equal opportunities alongside men. Theoretically, this study contributes to the discourse on gender and leadership in patriarchal societies, particularly in Islamic contexts. It underscores the significance of social capital and intellectual empowerment in enabling women to break traditional barriers and reshape societal norms.